Vous êtes sur la page 1sur 60

N 1

F C 1 (IR) s s = F (s)

|F (s)| < 1 [a, b] s

x 0 [a, b]

x n+1 = F(x n )

s

|F (s)| > 1

s

x

0

= s

  x n+1 = F(x n )

F C 1 (IR) F (s) = s |F (s)| < 1 F I = [s h, s + h] x I |F (x)| ≤ M ax(|F (x)| = |F (α)| < 1 (α I) F L = |F (α)| < 1 x I F (x) I |F (x) s| = |F (x) F (s)|

]s, x[ ]x, s[ |F (x) s| = |F ( )||x s|

T

⇒ |F ( )| < 1 |F (x) s| < |x s| < h F (x) I

x 0 I

x n+1 = F(x n )

s

|F (x)| < 1

|F (s)| > 1 F I = [s h, s + h] x I|F (x)| > 1

x 0

= s x n x n I

x n

I

x I |x n+1 s| = |F(x n ) F(s)| = |F ( )||x n s|( I) |x n+1 s| > |x n s| |F ( )| > 1 |x n+1 s| > |x n s| > |x 0 s|

x n

I |x n s| > h

n IN |x n s| ≥ min(|x 0 s|, h) > 0 (|x n s|) nIN 0 (x n ) nIN s

f C 2 [a, b]

f (a) < 0 f (b) > 0

f (x) > 0 f (x) > 0

x [a, b]

s f (x) = 0 f(x n )

x 0 = a

x n+1 = x n

f(b) f(x n )

b x n

n INx n s

x = 0

x n+1 s

x 0 = a s x n s

(f(s) f(x n ))(s x n )

f(x n ) f(b) f(x n ) b x n g(s x n

x n+1 = x n +

s x n b x n g(s x n ) g(b x n )

g(s x n )

x n+1 = x n

s x n

f(b) f(x n )

b x n

= x n +

) .(s x n )

g(b x n

= A 1

b x n x n + 1 = x n + A.(s x n ) x n + s x n = s

n IN

x n+1 = x n

b x n f (x) 0 x n < s f f (s) = 0 f(b) f(x n

x n s

f(x n )

f(b) f(x n )

> 0 x n < b x n+1 x n 0

b x n x n x n l x n+1 . f(l)

l

= l

f(l) = 0

n + 1 . f ( l ) l = l − ⇒ f ( l

f(b) f(l)

b l

x =

α x 0 [a, b]

1

2 cos x α [a, b]

x n+1 = 1 2 cos(x n ) n 0.

α

f (x) = x 1

1

2 cos x f (x) = 1 + 2 sin x

1

1

!α f (α) = 0 f (0) = 2 f (1) = 1 2 cos 1 > 0

F(x) = 1 2 cos x F (x) = 2 sin x

1

F

1

1

([0, 1]) = [ 2 cos 1, 2 ] [0, 1]

|F (x)| = 1

2 | sin x| <

1

2

F L = 1 2 < 1

x

0 [0, 1] x n+1 = F(x n ) = 1 2 cos(x n ) α

a (a > 0)

x 0

= α

1

x n+1 = 2 (x n +

a

x

n

)

n+1 a = x

2

2

x

(x n )

n a 2x n

2

, n 0 x n > a n 1

2

e n+1 = 2x e n

n

e n = a x n

Rel(x n+1 ) =

1

2x n

[Rel(x n )] 2 n 0 Rel(x n ) = x n x n1 x n

x 2 a = 0

(f (x) = 0)

; x 0 > 0 x 0 = a.

x n+1 = x n f(x n ) ) = x n x

f

(x n

n a

2x n

2

=x n+1 =

1

2 (x n +

a

x

n

)

= x

n + a

2

2x n

x

n+1 a = x

2

n a 2x n

2

2

x

2

n+1 a =

=

=

=

=

=

=

1 2 x n +

n 2

a

x

a

1

4

1

x

2

n

+ 2a + a n a

x

2

x n 4 + 2ax n + a 2

x

2

n

2

2

a

2

a

4

x 4 n + 2ax n + a 2

4x

2

n

x 4 n + 2ax n + a 2 4ax

2

2

n

4x

2

n

x 4 n 2ax n + a 2

2

4x

2

n

x

n a

2x

2

n

2

2

n 1 ; x n > a

n = 0 x 2

1

a = x

2

0 a

2x

2

0

2

> 0 (x 0

= a)

x 2 > a

1

1

x 1 > a x 1 > 0 x 1 = 2 (x 0 +

a 0 )

x

x n > a x n+1 > a

2 2 n − a 2x n 1 2 2 x > 0 ⇒ x
2
2
n − a
2x n
1
2
2
x
> 0 ⇒ x n+1 > a x n+1 =
2 (x n +
n+1 − a = x
x n+1 > √ a ⇒ ∀n ≥ 1 x n > √ a
1
a
x n+1 − x n = 1 2 (x n +
a ) − x n = − 2 x n +
x
2x n
n
2
= a − x
n
2x n
2
a − x
n
2x n > 0
< 0 x n > √ a
2x n
(x n )
e n = √ a − x n
e
=
√ a − x n+1
n+1
1
a
=
√ a − 2 (x n +
)
x n
2
2. √ a.x n − x n − a

=

2x n

= x

= (x n a) 2

n 2 2. a.x n + ( a) 2

2x n

2x n

2

e n+1 = 2x e n

n

2

n

Rel(x n+1 ) = x n+1 x n = a 2x n x

x n a = x

2

2 n1 a

2x n1

2

= [Rel(x n )] 2

Rel(x n+1 ) = 2x 1 n [Rel(x n )] 2

= x

n 2 a

2x n

a

x

n

) > 0

f(x) =

x

si

x

x 0

si

x 0

f(x) =

x 2 x 2

3

3

si

si

x 0 x 0

x 0 > 0

x 1 = x 0

f(x 0 ) ) =

f

(x 0

f(x 0 ) x = x 0 − 1 f (x 0 ) √ x
f(x 0 )
x
= x 0 −
1
f (x 0 )
√ x 0
x 0 −
= x 0 − 2x 0 = −x 0
1
2 √ x 0

x 1 = x 0 x 0 < 0

x 1 = x 0

f(x 0 ) ) = x 0 +

f

(x 0

x 0

1

2 x 0

x 1 = x 0 2x 0 = x 0 x 0 > 0x 1 = x 0 x 0 < 0x 1 = x 0 x 1 = (1) n x 0 x n = (1) n x 0 n = 0 n = 1 x n = (1) n x 0 x n+1 = (1) n+1 x 0

x n+1 = x n =

(1) n x 0 = (1) n+1 x 0

x n = (1) n x 0

x

0

=

0

0

x 2 si x 0 x 2 si x 0

3

3

x 1 = x 0 f(x 0 )

x 0 > 0

f

(x 0 )

x 1 = x 0

f(x 0 ) ) =

f

(x 0

x 0

2

3

x

0

1

3

0

2 3 x

=

x 0 3 x 0 = 2 x 0

2

1

x 0 < 0

x 1 = x 0

f(x 0 ) ) = x 0

f

(x 0

2 2

3

3

0

1

x

0

2

3

x

3

x

= x 0

2

3 x

1

3

x n = ( 1 ) n x 0

2

=

x 0 3 x 0 = 1

2

2

x 0

n = 0 n = 1

x n = ( 1 ) n x 0 x n+1 = ( 1

2

1 ( 1

2

x n = ( 1 ) n x 0

x

2

1

) n x 0 = ( 1

2

x n+1 = ( 2 )x 0 =

0

=

0

2

) n+1 x 0

2

) n+1 x 0

0

x n+1 = x n (x

2

n 2 + 3a)

3x n + a

a

,

n 0

lim n0

a x n+1

( a x n ) 3

x n+1 = F(x n ) F (x) = x(x 3x 2 2 + + 3a) a

F (x) = (3x 2 + 3a)(3x 2 + a) 6x 2 (3a + x 2

(3x 2 + a) 2

F ( a) = 24a 24a

(4a) 2 F (x) = 18a 5 + 12ax 3 30a 2 x

= 0

(3x 2 + a) 3

F ( a) = 18a 2 a + 12a 2 a 30a 2 a (4a) 3

F (3) (x) =

a

= 0

etF (3) ( a) = 0

lim

n+

a x n+1

( a x n ) 3

=

F (3) ( a)

3!

f IR \ {0} f (x) = x 1

x

e x

f f (x) = 0

g(x) = 1 + xe x

g(x) = ln(

x

x 1 )

g(x) = (x 1)e x x 0 x n+1 = g(x n )

x 0

x 0

f(x) = x 1

x

e x

f IR \ 0.

f (x) =

1

x 2 + e x > 0

 

x

−∞

0

 

+

f

(x)

 

+

   

+

f(x)

 
f ( x )   + ∞     11

+

   
f ( x )   + ∞     11

11

−∞−∞

 

−∞

s 1 s 2

f (1) = e 1 < 0 f (2) =

s 1 [1, 0[ s 2 [1, 2]

g(x) = 1 + xe x g (x) = e x xe x = e x (1 x) g”(x) = e x (1 x) e x = e x (2 x)

1

2

1 2 > 0 f (1) = 2 e < 0

e

 

x

 

1

s

2

2

g”(x)

 

   

00

    00  
 

g

(x)

   

1

1

   

2

e e 2

 

x

1

 

s

1

0

g”(x)

 

g

(x)

 

22ee

g ( x )   22 ee 11

11

g (s 1 ) > 1 x n s 1

 
 

x

 

1

2

g

(x)

 

g(x)

1

1

+

+

1 1

e e

1 1 e e

1

1

+

+

2 2 e e 2

2

g([1, 2]) = 1 +

2 2 , 1 + 1

e

e [1, 2]

|g (x)| ≤ 1 2 < 1 g

e

x 0 [1, 2]

x n+1 =

g(x n )

s 2

g(x) = ln(

D g = {x IR/

D

D g =] − ∞, 0[]1, +[

x

x 1 )

x

x 1 >

0}

g

= {x IR/x(x 1) > 0}

g (x) = (x 1) x x(x 1)

1

x(x 1) 2x 1

(x(x 1)) 2

1

2

) =

g(x) = x (x(x + (x − − 1)) 1) 2 ) =

g”(x) > 0 2x 1 > 0 x >

x

1

s

2

2

g”(x)

 

+

   

1

1

g (x)

 
g ( x )   2 2

2 2

−∞−∞

g (x) = 1

1

1) = 1 x 2 x 1 = 0

x(x

x 1 = 1 5

2

x 2

= 1 + 5

2

x 2 [1, 2] α = 1 + 2 5

> 0

f(α) = α 1

α

e α 0.18 > 0

s 2 ]1, α[; |g (x)| > 1 x n s 2

f (x) = x 3 x 2 1 f

f l 1 2

x 0 [1, 2]

x n+1

= x n x n + x n 1

3

2

x n+1 =

1

2

x n x n

2

x n+1 = (x n + 1)

1

3

l

f(x) = x 3 x 2 1

f (x) = 3x 2 2x = x(3x 2)

   

2

 

x

−∞

0

 

3

+

f

(x)

 

+

0

 

0

+

   
    −− 11   31 31 ++ ∞∞

−−11

    −− 11   31 31 ++ ∞∞
 

31

31

31 31

++∞∞

f(x)

 

−∞−∞

27

27

f

f (1) = 1 f (2) = 3 l [1, 2]

2

3 l >

2

3

x n+1 = F(x n )

F (x) = x 3 x 2 + x + 1

F

(x) = 3x 2 2x + 1

F

”(x) = 6x 2

|F (l)| > 2 (x n ) l

x n+1 =

1

2

x n x n

=

F(x n )

1 x x ]1, 2[ 2x 1

x

2

F(x) =

F (x) =

(x 2 x) 2 F (x) = 2(x 2 + x) 2 2(x 2 x)(2x 1) 2

(x 2 x) 4 F (x) = 2(x 2 + x) 2(2x 1) 2 (x 2 x) 3

F

(x) = 2x 2 2x 8x 2 2 + 8x x 3 (x 1) 3

(x) = 2(3x 2 3x + 1) x 3 (x 1) 3

F

num = 9 12 = 3 < 0 Num > 0 F ”(x) > 0 ]1, 2[ F (x) = 1

 

x

1

 

2

F

”(x)

   

+

   

3

3

F

(x)

 
F ( x )   4 4

4

4

 

−∞−∞

f (1) = 1 f ( 3 ) = ( 3 ) 3 ( 3 ) 2 1 = 8 > 0

2

2

2

1

l [1,

7

4

]

x [1, 7 ] F (x) ≤ − 40

21

4

F (l) < 40

21

|F (l)| > 40

21

(x n ) nIN l

> 1

f (x) = 0 x 3 x 2 1 = 0 x 3 = x 2 + 1 x = x 2 + 1

x n+1 = F(x n ) F(x) = (x 2 + 1)

F

3

1

3

(x) = 2 3 x(x 2 + 1) 2

3

F ”(x) = 2 3 (x 2 + 1) 3 8

2

9 x 2 (x 2 + 1) 5

3

F ”(x) = 8

9 (x 2 + 1) 3 (

2

3

4

2

x + 1 ) 3 4

x

2

x 2 x 2 + 1

3x 2 + 3 4x 2

 

3 x 2 1) = ( 3 x)( 3 + x)

4(x 2 +

4(